Rancang Bangun Desain Ui/Ux Pada Pembuatan Startup Aplikasi Selfcare Berbasis Website - M Lutfi Akbar; Ari Usman; Arief Budiman (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
During this pandemic, people are advised not to make physical contact and meet people who are not important. And many various product sellers switch to e-commerce or website-based online transactions, in making the website it is very necessary to have an attractive UI/UX design. In making the UI/UX design display, an application called figma is needed. Therefore, the researcher will design and build a UI/UX design in making a website-based selfcare application to make it easier for customers and sellers to transact buying and selling these products.